ACTN3 R577X Polymorphism and Neuromuscular Response to Resistance Training - Gentil, Paulo (Asist Group, 2011)
The R577X polymorphism at the ACTN3 gene has been associated with muscle strength, hypertrophy and athletic status. The X allele, which is associated with the absence of ACTN3 protein is supposed to impair performance of high force/velocity muscle contractions. The purpose of the present study was to investigate the association of the R577X polymorphism with the muscle response to resistance training in young men. One hundred forty one men performed two resistance training sessions per week for 11 weeks. Participants were tested for 1RM bench press, knee extensors peak torque, and knee extensors muscle thickness at baseline and after the training period. Genotyping was conducted using de DdeI restriction enzyme. Genotype distribution was 34.4% for RR, 47% for RX and 18.6% for the XX genotype. According to the results, the R577X polymorphism at the ACTN3 gene is not associated with baseline muscle strength or with the muscle strength response to resistance training. However, only carriers of the R allele showed increases in muscle thickness in response to training.